Delivering analysis in the IDS to inform policy implementation – Child Fuel Poverty - Yule, Phil; Hartley-Binns, James; Brunner, Franziska; Wise, Tom (International Journal of Population Data Science, 2025)
Objectives Administrative data hold great potential for generating evidence for policy supporting issues and government missions. Our initial explorations typically examine whether the variables and indexes within the data held on the Integrated Data Service (IDS) provide a viable way to link this data, giving new policy insights to address issues. Methods Within IDS we essentially have three major spines, one Demographic index is basically a spine of all people in the UK, the Business index for businesses and the Address index covers all UPRN level addresses. The interesting part, of course, comes as a result of linking between those spines with data like the Census 2011/2021, Births, Labour Force Survey and HMRC’s PAYE RTI to name a few. This potentially unlocks the answers to policy questions from across government, vis-a-vis, household composition, or health and educational outcomes and much, much more. Result The IDS is a cross-government initiative, designed to transform the way de-identified data is made available for vital research and decision-making about our society and economy. Working collaboratively and using the power of linked data within the IDS, with key datasets acting as the spine of this research, we plan to provide policy makers with robust and collaborative evidence, to inform the decisions made across UK to improve people’s lives. This is an opportunity to engage with the research community and explore a new approach for IDS and ONS’s TRE offering. For example, we have recently commenced some fascinating research around child fuel poverty and this will accelerate throughout 2025. By the time of the conference, interesting insights and analysis will be ready to share with delegates. Conclusion This project improves understanding of Britain’s fuel poverty, the types of homes and households with children affected, economic drivers and geographic areas most impacted. Policy interventions, such as social tariffs, to alleviate hardship form part of the analysis. In time, health and educational outcomes could form part of iterative research.